The Importance of Ethical Decision-Making in Nursing Practice - Jehan Madhour Alshammary, Albandri Abdulaziz Alnasser, Halima Abdullah Al Yami, Abdullah Mobark Almsaen, Fatimah Ahmad Sadly; Mona Jamaan Aldossary, Amal Khalaf Essa Al-anazi, Mashael Mahdi Alqahtani, Maryam awad alanazi, Jamilah muteq Alrashidi, Hala Swilah Almotairi (Journal of International Crisis and Risk Communication Research, 2024)
Ethical decision-making is a cornerstone of nursing practice, as nurses navigate complex situations involving moral dilemmas, conflicting values, and challenging choices. The COVID-19 pandemic has brought unprecedented ethical challenges to the forefront, testing the resilience and moral fortitude of nurses worldwide. This comprehensive paper explores the significance of ethical decision-making in nursing practice, examining its foundations in ethical principles, professional codes of conduct, and the unique challenges posed by the pandemic. The paper delves into the ethical dilemmas nurses have faced during the COVID-19 crisis, including resource allocation, end-of-life care, healthcare worker safety, health equity, decision-making in crisis situations, balancing clinical and public health ethics, ethical considerations in research and data collection, and challenges in long-term care and community settings. These challenges highlight the importance of robust ethical frameworks, education, and support systems for nurses. Strategies for promoting ethical decision-making in nursing practice are discussed, encompassing ethical education and training, decision-making models and frameworks, ethical committees and consultation services, ethical leadership and role modeling, interprofessional collaboration, ongoing ethical reflection and discourse, institutional support and resources, emotional support and resilience building, policy development and advocacy, and continuous quality improvement and learning. By cultivating ethical competence and fostering a culture of ethical decision-making, healthcare organizations can ensure that patient care is delivered with the highest ethical standards, upholding principles of beneficence, non-maleficence, respect for autonomy, justice, and fidelity. Ultimately, ethical decision-making is a moral imperative, enabling nurses to maintain the trust and confidence of individuals and communities while contributing to ethical and equitable healthcare systems.